PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS VB SD NEGERI 187 PEKANBARU - Anjani, Lidya; Noviana, Eddy; Witri, Gustimal (Universitas Pendidikan Indonesia, 2021)
This study aims to improve learning outcomes in Civics subjects in class VB SD Negeri 187 Pekanbaru for the 2019/2020 academic year through the application of the make a match type of cooperative learning model. This research is a Classroom Action Research (CAR) which was conducted in two cycles. Each cycle consists of two meetings to deliver the material and one daily test meeting. In order for the classroom action research to be successful, the researcher arranged the stages, namely planning, implementing, observing, reflecting. The subjects of this study were students of class VB SD Negeri 187 Pekanbaru with a total of 36 students. Data collection instruments in this thesis are teacher activity sheets and student activities and learning outcomes. The results showed that the low student learning outcomes of Civics as seen from the completeness of student learning outcomes with KKM 70 out of 36 students who reached KKM was only 10 (27.78%) while 26 (72.22%) students had not reached KKM with an average score of 59. , 44. Based on the research results, it is concluded that there is an increase in learning outcomes seen in the average value of the basic score, namely 59.44, increasing by 16.37% to 69.17 at UH I then increasing again by 37.15% to 81.52 in UH II proves that the application of the make a match cooperative model can improve the learning outcomes of Civics for class VB students of SD Negeri 187Pekanbaru